Exploring Multimodal Text Practice among Junior High School EFL Teachers: A Case Study - Wara Wahyuningrum, Dwi; Sumardi , Sumardi; Setyaningsih, Endang (International Journal of Educational Research & Social Sciences, 2024)
The increasing popularity of multimodal text in the digital era is due to its capacity to facilitate more interactive and engaging communication. These texts employ a variety of modes of communication, including text, images, sound, video, and gestures. This research aims to describe how teachers incorporate multimodal text into their English as a Foreign Language (EFL) writing classrooms. This research used a qualitative case study approach to examine two EFL teachers who teach in private secondary school in Indonesia. The research collected data through classroom observations, employing a qualitative case study approach. The researchers identified how teachers incorporate the use of multimodal texts in writing classes, specifically in relation to planning, organizing, identifying, and evaluating in the English as a Foreign Language (EFL) classroom. Further research is necessary to determine the impact of using multimodal texts in EFL writing classes